Development of a mobility aid for paraplegics in rural areas - Bartels, Heinrich (My University, 2014)
At present there exists no adequate mobility aid designed for rural areas in Southern Africa and paraplegics have difficulty in negotiating rough ground with conventional wheelchairs. Specifications for a suitable mobility aid were developed after interviewing paraplegics in Lesotho and Bophuthatswana, and after conducting tests by personally riding a conventional wheelchair in those areas. After considering various options, a four-wheeled chain driven vehicle was chosen because it satisfies most of the specifications. The proposed design is a compromise which emphasises improved mobility outdoors. It is able to enter houses, climb gradients of 1:5 and will cost about R700 to manufacture. A prototype was built and initial tests indicated the need for some modifications but confirmed the main advantages. However, further trials will be needed to test the robustness of the design before considering subsequent development.
MSc(E.ng) Dissertation 17 December 1989